The Influence of Socioemotional Wealth on Entrepreneurial Orientation and Business Performance in Family Business - Ni Made Erina Arya Puspita (Universitas Ciputra Surabaya, 2023)
This research aims to analyze the influence of Socioemotional Wealth and Entrepreneurial Orientation towards Business Performance of Family Business. The background of this research is the decline of family businesses, especially when passing over to the second generation, due to the lack of attention of succession in the family businesses' long-term orientation. Thus, Socioemotional Wealth and Entrepreneurial Orientation are suggested to provide significant influence on the family businesses' Business Performance, especially in helping to maintain and passing the succession to the next generation. This research is a quantitative research analyzed using SEM-PLS. questionnaire The data is gathered from 60 respondents, who are members of UC Family Business Community, using online questionnaire with likert scale, and is calcultated using sampling method called